A Method for the Selection of Rock Support Based on Bolt Loading Measurements - Stephen P. Signer (International Conference on Ground Control in Mining, 1997)
A method to assist in the evaluation and selection of roof bolts using in situ measurements of roof bolt loading has been developed by researchers of the Spokane Research Center, National Institute of Occupational Safety and Health. Both axial and bending forces are measured by strain gauges at many locations along the length of fully grouted bolts during various stages of mining. This information is then used to ( I) predict bolt loading for variations in bolt spacing, grade, and diameter, (2) calculate the design changes necessary in zones where bending loads are high, and (3) determine if bolt length is adequate. Results from several case studies of full-column bolt loading in coal mine gate roads are used to illustrate the design method. This knowledge will give design engineers a tool for the selection of roof support systems that will improve underground safety by reducing roof bolt failures.